Spiritual Reports from Long-Term HIV Survivors: Reclaiming Meaning While Confronting Mortality - Desrosiers, Kyle (Religions, 2020)
Reports from Long-term HIV Survivors: Reclaiming Meaning while Confronting Mortality presents research completed by Kyle Desrosiers in conjunction with the Baylor University Institute for Oral History. Applying lifespan theory to spiritual development, it discusses the narratives of four American long-term HIV survivors from Latter-day Saints, Roman Catholic (2), and Conservative Jewish backgrounds. The fifth profile is from a Protestant pastor with an HIV ministry in a rural area. These profiles are five selected from among 10 interviews with HIV-positive people and caregivers across America now archived by the author at Baylor University. Questions directing this research were: how does HIV status affect participants’ relationship to their religious communities, identities, and spiritualties?; what narratives emerge from lifespan perspectives of HIV-positive and queer participants?; and what spiritual practices, mythos, and beliefs evolve/remain as a product of living at the margins of religion and society, alongside coping with a deadly global epidemic? This project reports narratives of change, continuity, and meaning-making to discuss how several gay/queer men from a range of ethnic and faith backgrounds have used spirituality and worldview to navigate life.